(untitled) (The Research of Medical Science Review, 2024)
Different serotypes of the dengue virus and spread by the mosquito Aedes aegypti. Sometimes it progresses to be known as dengue hemorrhagic fever (DHF) and dengue shock syndrome, making it a global health threat. Measures aimed at preventing its effects are hinged on exploiting the management of water supply and avoiding contact with mosquitoes, especially in the developing or less developed areas. This study aimed to assess the level of knowledge and awareness regarding dengue fever and its prevention among the rural community of Tando Allahyar. A cross sectional was carried out for three months with male and female residents. A non-probability convenience sampling method was used while selecting the participants. Data analysis was done using IBM SPSS version 23, with descriptive statistics used to present demographic data and study variables. This finding indicated that 38.7% of the respondents were male and 61.3% were female. 73.3% of the participants had no education, while 12.0% completed their primary education, 8.0% had secondary education, and the remaining 6.6% had a higher level of education. The majority of participants reported having heard about dengue fever. Nevertheless, various knowledge gaps concerning the disease transmission, signs and symptoms, and prevention were revealed, including poor awareness of which type of mosquito transmits the disease. The study concluded that there is high concern for better knowledge and health promotion regarding dengue fever. Using good and sustained public health promotion measures, there will be an increase in awareness among the people, and in effect, reduction the the incidences of dengue fever.